2003
DOI: 10.1016/j.cub.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Analysis of 60 G Protein-Coupled Receptors in Caenorhabditis elegans by Gene Knockout with RNAi

Abstract: G protein-coupled receptors (GPCRs) are the largest family of genes in animal genomes and represent more than 2% of genes in humans and C. elegans. These evolutionarily conserved seven-transmembrane proteins transduce a diverse range of signals. In view of their pivotal role in cell signaling, it is perhaps surprising that decades of genetic analysis in C. elegans, and recent genome-wide RNAi screens, have identified very few GPCR mutants. Therefore, we screened all GPCRs predicted to bind either small-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 26 publications
2
122
1
Order By: Relevance
“…High-throughput RNAi analyses have previously been used to study gene function in D. melanogaster and C. elegans. For example, essential genes (22), G protein-coupled receptors (GPCRs) (23), fat regulatory genes (24), and genes that regulate lifespan (25) have been functionally analyzed by this approach. Unfortunately, similar studies in mammals still represent a technological challenge.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput RNAi analyses have previously been used to study gene function in D. melanogaster and C. elegans. For example, essential genes (22), G protein-coupled receptors (GPCRs) (23), fat regulatory genes (24), and genes that regulate lifespan (25) have been functionally analyzed by this approach. Unfortunately, similar studies in mammals still represent a technological challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Many neuropeptides and neuropeptide receptors are known to influence muscle and neuronal activity and ultimately locomotion in C. elegans and other nematodes (Marks et al 2001;Rogers et al 2001;Keating et al 2003;Husson et al 2007). It is possible that one or more neuromodulators required to regulate locomotion are released from neuronal DCVs in wild-type animals but are not transported properly through the neuronal secretory pathway in unc-73 RhoGEF-2 or rab-2 mutants and not properly released from unc-31 mutant neurons.…”
Section: Unc-73 Rhogef-2 Isoforms and Neuromodulatory Protein Signalingmentioning
confidence: 99%
“…However, when reproduction is considered, Keating and coworkers [21] very recently found that RNAi of the presently identified VRFamide receptor 1 on N2 animals resulted in a statistically significant increase in the number of progeny counted 48 h post-L4. The precise mechanism underlying the RNAi effects on egg laying and brood size were not determined in the latter study.…”
Section: Discussionmentioning
confidence: 99%